Economic Policy Choices and Economic Growth of Nigeria: Lessons from the Asian Pacific - Obuareghe, Goddey; Dike, Jude (PT. Riset Press International, 2025)
This study examined the effect of economic policy choices on the growth of Nigeria with specific reference to the Asian Pacific from 1994 to 2022 (i.e. 29 years). Specifically, the study covered three (3) variables. The three economic policy variables are broad money supply, total trade and government revenue. The three economic policy variables accounted for monetary, trade and fiscal policy measures. Meanwhile, the economic growth proxy is considered to be real gross domestic product (RGDP). Data were retrieved from the Central Bank of Nigeria Statistical Bulletin, 2022. The robust regression analysis was suitable for the study. The study confirmed that the broad money supply negatively affects economic growth. However, total trade and government revenue positively affected economic growth. Overall, the study concludes that economic policy choices have a mixed effect on the growth of the Nigerian economy. As such, the Nigerian government should use its monetary policy tools to curb excess cash from circulation. Further, efforts should be made to reduce some trade barriers that mitigate successful trading in Nigeria. Lastly, the Nigerian government should reappraise the country's current trade policies, as this may be the main reason the Nigerian economy is still underdeveloped.